TURN-TAKING STRATEGIES USED IN A CONVERSATION WITH BILL GATES IN HARVAD UNIVERSITY YOUTUBE CHANNEL - Rahmah, Nur; Halim, Abdul (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study was aimed at finding out t what type of turn-taking strategies are used by Bill Gates and David in the Harvard campaign to launch William H. Gates and how are the turn allocation in turn-taking strategies used by Bill Gates and David in the Harvard campaign launch of William H. Gates. A qualitative methodology was employed for examining this research. The data collection technique used in this research was to download the video, watch the video, listen repeatedly and carefully to understand the content of the conversation, and notice the turn-taking strategy used by Bil and David. As a result, Stenstrom's theory is applied in this study. (1994) and Sacks, Schegloff, and Jefferson (1974) to answer research questions. The purpose of this study is to discover the kind of turn-taking. (Taking the turn, Holding the turn, Yielding the turn) and how turn allocation works (selecting the next speaker, self- select, the speaker continues). The research findings revealed that the 20 data of turn-taking strategy types in this study were taking the floor (10 data), holding the floor (8 data) and yielding the floor (7 data). The researcher then discovers the third turn allocation of turn-taking strategies. the findings data for the turn-allocation of turn-taking strategies were the technique The researcher then used the turn- taking strategy to determine the third turn allocation. The current speaker selecting the following speaker (12 data) for the self-selection technique (10 data) and the current speaker continuing (1) From these findings, the tur-taking helps the conversation flow smoothly. It implies that everyone in the discussion is responsible for preventing overlapping talk. Listeners sometimes enjoy taking turns using allocations of their choosing.